Tafasitamab for the treatment of relapsed or refractory diffuse large B-cell lymphoma - Salles, Gilles; Długosz-Danecka, Monika; Ghesquières, Hervé; Jurczak, Wojciech (Expert opinion on biological therapy, 2021)
Patients with relapsed or refractory diffuse large B-cell lymphoma (R/R DLBCL) require further treatment options, especially in cases that cannot tolerate stem cell transplant or cytotoxic chemotherapy. CD19 has emerged as an attractive target in B-cell malignancy and is the subject of several therapeutic strategies. The anti-CD19, humanized, monoclonal antibody tafasitamab (MOR208) has an engineered, modified Fc region with increased affinity for Fcγ receptors, leading to increased cytotoxicity via natural killer cells and macrophages (antibody-dependent cellular cytotoxicity and antibody-dependent cell-mediated phagocytosis) in a promising approach. The development of tafasitamab is reviewed, together with the pharmacokinetics and clinical experience of tafasitamab in R/R DLBCL; clinical data have led to FDA approval and inclusion in NCCN treatment guidelines for tafasitamab in combination with lenalidomide in this indication. Patients with R/R DLBCL who have failed rituximab-containing regimens may be resistant to CD20-directed therapies; therefore, therapies with an alternative mode of action are of great interest in this setting. Tafasitamab, an anti-CD19 monoclonal antibody, in combination with lenalidomide has demonstrated promising efficacy for patients with R/R DLBCL who are ineligible for autologous stem cell transplantation. This could provide an alternative approach to classical chemotherapy-based regimens in the relapsed setting.